2012
DOI: 10.1380/ejssnt.2012.569
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Yellowing of Ancient Paper

Abstract: Paper is the most widely used writing support due to the remarkable properties of its principal componentcellulose -one of the most abundant biomaterials present on Earth. However, due to the complexity of the material, an exhaustive picture of its degradation pathways is still missing. In this paper, we will present recent results and progresses obtained in the comprehension of the role of cellulose oxidation in the yellowing of ancient paper. Visible and ultraviolet spectra of cellulose in ancient paper samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This increasing is even larger in Damascus samples 529 and 17 (see Table 2), where the relative concentrations of M2H and CHO are comparable. Other studies have shown that this result is typical for samples aged in high humidity environment [77,81]. We also note that CC oxidized group is always absent in all the samples.…”
Section: Ccosupporting
confidence: 84%
“…This increasing is even larger in Damascus samples 529 and 17 (see Table 2), where the relative concentrations of M2H and CHO are comparable. Other studies have shown that this result is typical for samples aged in high humidity environment [77,81]. We also note that CC oxidized group is always absent in all the samples.…”
Section: Ccosupporting
confidence: 84%
“…Pristine cellulose does not absorb light above about 200 nm (below 6 eV) [8,18]. The yellow color seen in aged papers is mainly due to the fact that chromophores in paper absorb the higher energy band of visible light (corresponding to violet and blue) and largely scatter the yellow and red portion, thereby producing the characteristic yellow-brown hue [8,15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…2(b)). The linear combination coefficients obtained give an estimation of the concentration of chromophores inside aged paper, 20,21 and make it possible to obtain chemical information on the self-portrait by entirely non-destructive and non-invasive optical measurements.…”
mentioning
confidence: 99%